81 Family Perceptions of TRaC-K (Telehealth Rounding and Consultation for Kids) a Novel Inpatient Tertiary Regional Virtual Health Collaborative. (21st October 2022) - Bailey, Michelle; Bele, Sumedh; Randhawa, Alam; deGuzman, Elizabeth; Montgomery, Lara; Ritchie, Courtney
Abstract: Background: Telehealth Rounding and Consultation for Kids (TRaC-K) is an innovative virtual tertiary-regional collaborative care service for regional pediatric inpatients launched in Southern Alberta in August 2020. TRaC-K uses a mobile audiovisual platform to connect regional and tertiary pediatricians and multidisciplinary clinicians caring for admitted children from Southeastern Alberta. The mobile cart also enables children and families to participate in TRaC-K sessions at the bedside. The TRaC-K model is being evaluated during a 1 year pilot between the Alberta Children's Hospital (ACH) and the Medicine Hat Regional Hospital (MHRH). Objectives: As part of the evaluation of the TRaC-K model, we aimed to explore family perceptions of their experience participating in one or more TRaC-K sessions. Design/Methods: Family perceptions of receiving care using the TRaC-K model were explored using qualitative analysis of family interviews. Semi-structured interviews were conducted with consenting families who had participated in one or more TRaC-K sessions while their child was admitted at ACH or MHRH. Interviews were conducted via ZOOM or telephone by a research coordinator experienced in qualitative interviews. A short questionnaire of participant information was completed. A series of questions were asked in addition to clarifying questions. Interviews were recorded, transcribed and the NVivo 12 Pro qualitative data analysis software was used for coding. Inductive thematic analysis was completed by two research team members and three transcriptions were coded by both and compared to ensure alignment in coding methodology. There were 15 transcriptions in total. Themes and subthemes were shared with the research team to validate the assignment of quotes to themes and further organize the themes and subthemes. Results: Of the 85 TRaC-K sessions during the one year pilot, 36 sessions included at least one family member participant. Of the family members participating in a TRaC-K session, 15 families completed an interview with contributions from one or more parents/guardians. Thematic analysis identified five themes and several subthemes. Themes included: 1. family centered care, 2. access to care closer to home with a subtheme of ease of transition, 3. enhances quality of care with a subtheme of assessment, 4. communication tool with subthemes of real time, technology, facilitates collaboration and shared decision making, and 5. increases family confidence. Conclusion: TRaC-K, a tertiary-regional inpatient virtual health model, was perceived by families to be beneficial to their child's care and their own experience with inpatient care. Families were able to identify many facets of their experience with this novel model of care. To enhance family centered care for families from outside large urban centers whose children require inpatient admission, virtual health models like TRaC-K that enable tertiary-regional clinician collaboration and family participation should be spread to other pediatric inpatient populations.